Project based Learning: DIY Learning Model to Write the Procedure Text at SMP N 4 Surakarta - Savira, S.Pd, Agus Tika Dwi; Susanti. S.Pd, Sinta Ari; Haryati, S.Pd, Rini Dwi; Setyawan, M.Pd, Dr. Budhi (Yudha English Gallery, 2023)
Writing is an aspect in language skill that should be mastered well by every student. Writing is the main skill that is fundamental for every student in memorizing and explaining the knowledge and insights that they gain. In the academic field, writing has even become a benchmark for assessing and evaluating the achievement of learning outcomes. However, in practice there are a few students who have quite low writing skills. The teacher's role in providing a learning space that develops writing skills is very necessary. This research provides an in-depth analysis of the DIY (Do It Yourself) learning model which can help students in writing skills, especially in writing procedural texts. Creating a procedure text must be coherent, clear and effective so that readers can follow the steps correctly. Therefore, students are required to be able to write procedural texts well and correctly according to the structures and language features. This research used a qualitative descriptive analysis method based on case studies. The research objects were class VII C students at SMP N 4 Surakarta. The result of this study shows the DIY (Do It Yourself) learning model can help the students to write procedural texts easily using project based learning